Effects of the shape features of graphite nanoplatelets on electrically-conductive behaviors of polydimethylsiloxane-based stretchable electrodes. (19th June 2019) - Zhao, Hang; Yang, Minhao; He, Delong; Liu, Yu; Bai, Jintao; Bai, Jinbo
Abstract: Dielectric elastomers, featuring high energy conversion efficiency, actuator-generator dual mode, high response speed and broad applicable range, have attracted a huge surge of research interest with the fast developing new energy capture systems. As a critical component of dielectric elastomers, a pair of ideal stretchable electrodes can not only introduce sufficient charges onto elastomer surfaces, but also keep high electrical conductivity at large planar strains. Here, a series of compliant electrodes composed of graphite nanoplatelets (GNPs) with similar electrical properties but distinguishable shape features were prepared through a spray-coating process. The three types of GNPs have been used to study the effect of GNP shapes on the electrical resistance variation of the flexible electrodes under varied strain ratios. It was found that the GNP aspect ratio played a dominating role in the strain-dependent resistance change of GNPs electrodes. When applying a uniaxial strain of 0.6, the GNPs electrodes possessing aspect ratios values around 80 and 1800 showed the relative resistance variation of 980% and 200%, respectively. Moreover, the utilized theoretical fitting was benefit to deeply study the electrically-conductive behaviors of compliant electrodes. This study would provide useful suggestions for the future design of compliant electrodes.